PERAN SEKOLAH DALAM MENANGGULANGI PERILAKU KENAKALAN REMAJA DI SMK TERPADU BISMILLAH KECAMATAN PADARINCANG KABUPATEN SERANG - Polelah; Subhan Widiansyah; Dema Tesniyadi (STKIP Subang, 2023)
This study describes the role of schools in dealing with juvenile delinquency behavior at Bismillah Integrated Vocational School, Padarincang District, Serang Regency. The purpose of this research was to find out and analyze the forms of juvenile delinquency carried out by students at school, factors that can cause juvenile delinquency or violations at school, school constraints and efforts or school actions in tackling juvenile delinquency behavior that occurs at Bismillah Integrated Vocational School This. In this case the forms of juvenile delinquency that occur at the Bismillah Integrated Vocational School are such as truancy, making class noise, smoking, arriving late, excessive dating, online game addiction, disrespectful attitude towards teachers and fellow friends and several other disciplinary delinquencies. Furthermore, namely the causative factors or factors for the emergence of juvenile delinquency that occurred at Bismillah Integrated Vocational School, Padarincang District, Serang Regency, there are two kinds, namely internal factors and external factors. In addition, it is also hoped that this research can provide benefits for schools to help overcome juvenile delinquency behavior in schools by seeking countermeasures, namely preventive, repressive and curative efforts.